INVESTISSEMENTS DIRECTS ETRANGERS ET INEGALITE DE REVENUS EN REPUBLIQUE DEMOCRATIQUE DU CONGO - Marcel, SENGA PESSE (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2025)
This article generally aimed to demonstrate how Foreign Direct Investment (FDI) influences income inequality in the Democratic Republic of Congo (DRC) from 1985 to 2020. Thus, to achieve this objective, the study used an analytical approach, supported by econometric tools, while using an autoregressive distributed lag model (ARDL), following the new cointegration approach of Pesaran et al. (2001). The documentary technique made it possible to collect all the essential data. In light of the results obtained after data analysis, the following major finding was drawn: FDI does not constitute a catalyst for the reduction of income inequalities in the DRC. This situation is justified by the challenges faced by foreign investors, the opportunities and policies that could promote the attraction of these investments in the country."